Design and Preliminary Validation of a Lower Limb Exoskeleton With Compact and Modular Actuation - Li, Yinbo; Guan, Xinyu; Han, Xinyu; Tang, Zihan; Meng, Kuilin; Shi, Zhanpeng; Penzlin, Bernhard; Yang, Yilin; Ren, Junli; Yang, Ze; Li, Zhibin; Leonhardt, Steffen; et al. (IEEE access, 2020)
Geared motor-driven lower limb exoskeletons (LLEs) are widely researched to assist paraplegic patients with spinal cord injury in recovering locomotion ability. In order to achieve a compact exoskeleton joint design while avoiding increasing the mechanical complexity of the exoskeleton frame, this study presents a design of an LLE with compact and modular actuation. A synchronous drive and a gear drive as transmissions are used to distribute hip and knee actuators, respectively, ensuring a compact axial width. The modular design of joint actuators enables it simple to separately design or select the ergonomic exoskeleton frames. A paradigm of the LLE design is comprehensively provided, including the requirement analysis, mechanical, electrical and control system design, which can be a reference of the early development of the exoskeleton prototype. The performance of the LLE is preliminarily validated by the benchtop tests including the closed-loop speed bandwidth test and the swing test and one healthy human subject experiments including walking with the LLE disenabling all motors and walking assisted by the LLE. The results of the benchtop tests validate that the LLE has enough bandwidth of closed-loop speed, satisfactory repeatability, high precision, good antijamming capability and strong torque capacity. The results of the healthy human subject experiments validate a harmonic interaction and a good integration between the user and the ergonomic mechanical system, good performance of the electrical and control system in joints motion control of the LLE. The prototype of the LLE smoothly and successfully assists the healthy human subject in walking on the level ground. The proposed LLE is promising to be applied to assist paraplegic patients in recovering the walking ability.